Lessons learnt from pandemic research with refugee communities - Sunita Joann Rebecca Healey; Nafiseh Ghafournia (Sax Institute, 2022)
Culturally and linguistically diverse (CALD) people are subject to many inequities worldwide, and research is no exception. We report lessons learnt as researchers conducting a qualitative study during the coronavirus disease 2019 (COVID-19) pandemic involving participants of refugee backgrounds. We found that despite the best intentions of the research team, a variety of factors in methodology and data collection presented unexpected barriers for our studied population. We share our reflections to assist others in their research endeavours. Researchers and institutions have a moral obligation to provide research practices that are both suitable and beneficial to the community. Collaborating with community members in the research process allows researchers to create ethically sound, practical studies with maximum utility.